2x + 5y = 2-3x - y = -3from the second equation:-y = -3 + 3xy = 3 - 3xsubstitute this value in the first equation:2x + 5(3-3x) = 22x + 15 - 15x = 2-13x + 15 = 2-13x = 2 - 15-13x = -13so, x = 1Now, solve for y :y = 3 - 3xy = 3 - 3 (1)y = zero
y-3x+6y=12 7y=3x+12 y=3x/7 +12/7
3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2
If: x-2y = 1 and 3xy -y^2 = 8 Then: x = 1+2y and 3(1+2y)y -y^2 = 8 Hence: 3y+6y^2 -y^2 = 8 => 5y^2 +3y -8 = 0 Solving the above quadratic equation: y =1 or y = -8/5 Solutions by substitution are: when y=1 then x=3 and when y=-8/5 then x=-11/5
x - 2y = 1 → x = 1 + 2y 3xy - y² = 8 Substitute the first equation into the second equation and subtract 8 from both sides: 3(1 +2y)y - y² = 0 3y +6y² - y² - 8 = 0 5y² + 3y - 8 = 0 When factored: (5y +8)(y -1) = 0 Therefore: y = -⁸/₅ or y = 1 Substituting the above values into the linear equation gives the solutions as: (3, 1) and (-¹¹/₈, -⁸/₅)
-2x-10y-12+3xy=4Put all x's to the other side and the ones with y's on the other:-10y+3xy=4+2x+12-10y+3xy=16+2xNow you factor a y from the side with the y's:y(-10+3x)=16+2xDivide both sides by (-10+3x):y=(16+2x)/(-10+3x)
yes 3xy=6
2x + 5y = 2-3x - y = -3from the second equation:-y = -3 + 3xy = 3 - 3xsubstitute this value in the first equation:2x + 5(3-3x) = 22x + 15 - 15x = 2-13x + 15 = 2-13x = 2 - 15-13x = -13so, x = 1Now, solve for y :y = 3 - 3xy = 3 - 3 (1)y = zero
M=3 because y+y+y= 3xY and MY= MxY
You plug in the values of x and y and solve 12x + 16y = ? 12(1) + 16(2) = 12 + 32 = 44
y-3x+6y=12 7y=3x+12 y=3x/7 +12/7
3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2
2x+3xy-4y=10to solve for yyour objective will be to get y by itself on one side of the equal signyou first subtract 2x to get the terms with y variables on one side3xy-4y=10-2xthen undistribute the y from the two terms to get one yy(3x-4)=10-2xnow divide 3x-4y=(10-2x)/(3x-4)theres your answer
in order to solve this problem you have to solve for x first wich you are given the data to pre forme so x=4 and x.2=8 and 8=y and y-4=4=a=x so a+8=12 and 12=b
If: x-2y = 1 and 3xy -y^2 = 8 Then: x = 1+2y and 3(1+2y)y -y^2 = 8 Hence: 3y+6y^2 -y^2 = 8 => 5y^2 +3y -8 = 0 Solving the above quadratic equation: y =1 or y = -8/5 Solutions by substitution are: when y=1 then x=3 and when y=-8/5 then x=-11/5
x - 2y = 1 → x = 1 + 2y 3xy - y² = 8 Substitute the first equation into the second equation and subtract 8 from both sides: 3(1 +2y)y - y² = 0 3y +6y² - y² - 8 = 0 5y² + 3y - 8 = 0 When factored: (5y +8)(y -1) = 0 Therefore: y = -⁸/₅ or y = 1 Substituting the above values into the linear equation gives the solutions as: (3, 1) and (-¹¹/₈, -⁸/₅)
3xy + 3y2 = 3y (x + y)